Cell Membrane‐Coated Lipid Nanoparticles for Drug Delivery - Moataz B. Zewail; Guangze Yang; Yilong Fan; Yue Hui; Chun‐Xia Zhao; Yun Liu (Aggregate)
ABSTRACT Cell membrane coating (CMC) of nanoparticles (NPs) has emerged as a prominent strategy that has gained significant attention and achieved notable progress across various therapeutic sectors. Coating NPs with natural cell membranes endows them with various functions and addresses various challenges in drug delivery, such as prolonging circulation time, reducing immunogenicity, and improving targeting efficiency and cellular communication. Among the different NPs, lipid nanoparticles (LNPs) have revolutionized the field of nanomedicine by providing various advantageous features for drug delivery. The versatile characteristics of LNPs synergize well with cell membranes’ biomimetic properties, creating hybrid structures with enhanced functionalities for diverse biomedical applications. A more advanced form of LNPs with significantly enhanced capabilities can be achieved through CMC. However, significant opportunities remain for further advancements, with ongoing efforts focused on discovering innovative applications and fully harnessing the potential of this promising combination. This article provides a critical review of recent progress in cell membrane coated‐LNPs (CMC‐LNPs). First, different LNP types, their preparation methods, and coating strategies are summarized. The development, properties, functions, and applications of CMC‐LNPs are then discussed. Last, their advantages, limitations, challenges, and future perspectives are presented.